FENOMENA PERUBAHAN DESAIN INTERIOR AREA BACA PERPUSTAKAAN UMUM JAKARTA CIKINI: THE PHENOMENON OF INTERIOR DESIGN CHANGES IN THE READING AREA OF THE JAKARTA CIKINI PUBLIC LIBRARY - Nadya Cindylaras; Juli Rianingrum, Cama; Joedawinata, Ahadiat (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
The Phenomenon of Interior Design Changes in the Reading Area of the Jakarta Cikini Public Library. Public libraries are experiencing functional changes due to societal needs and technological advancements. The Jakarta Cikini Regional Public Library, newly reopened in 2022 after revitalization, reflects this transformation. This research aims to observe changes in visitor activities and their impact on reading room facilities, comparing conditions before and after the implementation of creative activity concepts. The study provides an in-depth understanding of how interior library design evolves due to creative activities and adequate digital facilities. The method used is qualitative with a Historical-design Research approach, supported by the Theory of Change Phenomenon and Design Triangulation to determine the position of changes. The most significant change factor is the integration of digital technology, allowing visitors more flexibility to read or borrow books while relaxing or discussing.